2021
DOI: 10.5812/ijcm.113121
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment: Involved Factors and Signaling Pathways in Epithelial-Mesenchymal Transition

Abstract: Context: Metastasis is a main cause of death in patients with cancer, whereby tumor cells withdraw from the primary site of the tumor mass and produce secondary tumor mass in new sites. Primary tumor cells depart collectively and individually to invade closed and distant sites. Evidence Acquisition: This review considers TME-derived factors that actuate signaling pathways to induce epithelial-mesenchymal transition (EMT). National Center for Biotechnology Information (NCBI) was the main resource. Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Expression of E-cadherin, β-catenin, and γ-catenin is masked by TWIST1, but the expression of vimentin is increasing. Importantly, even a strong EMT-inducing transcription factor operates differentially in each cell type belonging to a different EMT status [ 48 , 49 ].…”
Section: Epigenetic Regulation Of Emt Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of E-cadherin, β-catenin, and γ-catenin is masked by TWIST1, but the expression of vimentin is increasing. Importantly, even a strong EMT-inducing transcription factor operates differentially in each cell type belonging to a different EMT status [ 48 , 49 ].…”
Section: Epigenetic Regulation Of Emt Biomarkersmentioning
confidence: 99%
“…Expression of E-cadherin, β-catenin, and γ-catenin is masked by TWIST1, but the expression of vimentin is increasing. Importantly, even a strong EMT-inducing transcription factor operates differentially in each cell type belonging to a different EMT status [48,49]. SNAI1 (Snail family transcriptional repressor 1) is the member of the SNAIL family that is the best studied EMT transcription factor and is predominantly expressed in cell lines with an epithelial phenotype.…”
Section: Transcription Factor Genesmentioning
confidence: 99%
“…In recent literature, TNBC has been proposed as the most aggressive group of breast cancer. Cell invasion is involved in the progression of breast cancer cell metastasis, and EMT-associated factors are a prominent feature of TNBC (5,6,19).…”
Section: Discussionmentioning
confidence: 99%
“…Meta stasis is a multi-stage process and is one of the most feared aspects of cancer mortality. In the first two stages, tumor cells detach from the basement membrane and extracellular matrix (5,6). Recent studies have shown that metastasis is closely related to the process of epithelia-mesenchymal transition (EMT) (7).…”
mentioning
confidence: 99%
“…The tyrosine kinase epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein that stimulates cell survival, mobility, growth, and proliferation (3,(11)(12)(13). This receptor is made of a single polypeptide chain with three domains (Figure 1) (14); the extracellular domain has five regions, including the ligand-binding site (14), the intracellular domain consisting of the regulatory region, tyrosine kinase, juxtamembrane, and lastly the transmembrane domain (14).…”
Section: Egfr/pten/akt/mtor Pathwaymentioning
confidence: 99%